Sign Language Interpreting in English Language Teaching for a Deaf Student: A case study - Adhika Irlang Suwiryo; Ellis Artyana (Indonesian JELT, 2018)
This paper discusses the case of appropriating a teaching approach as a response to the needs of a Deaf student registering to an English Department of a State University in Depok. The study particularly looks at the sign language interpreting practice in the classroom. In the teaching and learning process, the sign language interpreter has a significant role in transferring the course materials from the lecturer. In other words, the interpreter becomes one important factor for the student's achievement in acquiring the target language. However, there are several challenges faced by the interpreter in delivering the teaching content, such as, speech tempo, the usage of determiners (this, that), the usage of media, classroom preparation, and language differences (English and BISINDO—the natural sign language used by the Deaf community in Indonesia). The aim of this paper is to provide a clear picture concerning 1) sign language interpreting process in English teaching classroom, 2) the coordination of interpreter and lecturer(s), both in classroom preparation as well as teaching process, and 3) challenges experienced by the interpreter. Questionnaire and in-depth interviews are used with the lecturers, the student, and the interpreter in order to elicit as well as acknowledge the data related to the classroom preparation and teaching process. Data were transcribed, coded, and analyzed following interpretive paradigm. The results of this research offer suggestions in sign language interpreting process in English teaching classroom.